Reducing Laziness in Learning: A Review - Alida Vira Pramaesti; Iedialita Suprobo; Nurul Utami Putri; Rahil Khaunia Zindiqawati; Agrissto Bintang Aji Pradana (Prosiding University Research Colloquium, 2022)
Most individuals struggle with laziness. Failure, neglect, and other undesirable outcomes can result from laziness. Laziness, especially among students, may undoubtedly interfere with their learning efforts. The purpose of this study is to find techniques to reduce laziness in learning activities. This study used a semi-systematic review with ERIC as the journal database of choice. After doing a search in a variety of publications, 14 papers related to the topic of research were found. Laziness is said to be induced by both internal and external influences. According to the findings of this study, in order to reduce laziness, it is necessary to have self-awareness, facilities, and inspiration from others, such as teachers and parents.